FOS Expression in Osteoid Osteoma and Osteoblastoma: A Valuable Ancillary Diagnostic Tool. (December 2019) - Amary, Fernanda; Markert, Eva; Berisha, Fitim; Ye, Hongtao; Gerrand, Craig; Cool, Paul; Tirabosco, Roberto; Lindsay, Daniel; Pillay, Nischalan; O'Donnell, Paul; Baumhoer, Daniel; Flanagan, Adrienne M.
Abstract : Osteoblastoma and osteoid osteoma together are the most frequent benign bone-forming tumor, arbitrarily separated by size. In some instances, it can be difficult to differentiate osteoblastoma from osteosarcoma. Following our recent description of FOS gene rearrangement in these tumors, the aim of this study is to evaluate the value of immunohistochemistry in osteoid osteoma, osteoblastoma, and osteosarcoma for diagnostic purposes. A total of 337 cases were tested with antibodies against c-FOS: 84 osteoblastomas, 33 osteoid osteomas, 215 osteosarcomas, and 5 samples of reactive new bone formation. In all, 83% of osteoblastomas and 73% of osteoid osteoma showed significant expression of c-FOS in the osteoblastic tumor cell component. Of the osteosarcomas, 14% showed c-FOS expression, usually focal, and in areas with severe morphologic atypia which were unequivocally malignant: 4% showed more conspicuous expression, but these were negative for FOS gene rearrangement. We conclude that c-FOS immunoreactivity is present in the vast majority of osteoblastoma/osteoid osteoma, whereas its expression is usually focal or patchy, in no more than 14% of osteosarcoma biopsies. Therefore, any bone-forming tumor cases with worrying histologic features would benefit from fluorescence in situ hybridization analysis for FOS gene rearrangement. Our findings highlight the importance of undertaking a thorough assessment of expression patterns of antibodies in the light of morphologic, clinical, and radiologic features. Abstract : Supplemental Digital Content is available in the text.